Hubungan Nyeri Haid (Dismenore) dengan Aktivitas Belajar Sehari-Hari Pada Remaja Putri Kelas VII Di SMPN 3 Pulung. - sinta ayu setiawan; linda lestari (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2018)
Dysmenorrhea can affect more than half of women who have menstruation,and the reported prevalence varies considerably. The result of preliminary studyat SMPN 3 Pulung, Pulung Subdistrict, Ponorogo Regency, found that girls ofclass VII with a total of 53 students obtained data that 46 students hadexperienced menstrual pain (dysmenorrhea) and 7 female students have notexperienced menstruation. There are two primary dysmenorrhea and secondarydysmenorrhea, the factors affecting primary dysmenorrhea are <12 years. Neverhave a child, long period, smoking, obesity, and secondary dysmenorrheaEndometriosis, adenomyosis, IUD, Ovarian cyst. So that students who experiencedysmenorrhea sometimes have to ask permission to not follow the learningactivities because they can not stand the dysmenorrhea they experience. Thepurpose of this study was to find out the Relation of Menstrual Pain(Dysmenorrhea) with Young Women Learning Activity.This research wasconducted at SMPN 3 Pulung Pulung Subdistrict Ponorogo Regency onFebruary 9, 2017 type of research used is analitik. In this study the population ofall VII class students of teenage girls who experienced menstruation that waspresent during the study of 46 female students, the method used this samplingtechnique Accidental Sampling, the number of samples is 46 students In thisstudy the variables are Dysmenorrhea and Learning Activity. And analyzed bySpearman Rank statistical test. Based on the research results obtained thehighest level of pain is severe pain with a total of 37 female students (80,4%), itis known that the study activity criteria is disrupted with a total of 40 femalestudents (87%) respondents. Based on the calculation of Spearman Rankstatistical P=0.000 is less than 0.05 (P˂0.05) which means that Ho is rejectedand Ha accepted, it can be concluded that there is a relationship of painMenstruation (dysmenorrhea) to the daily learning activity in the second gradegirls in SMPN 3 Pulung with the level of corelation of 0.602 which means thestrong level of closeness. It is advisable for young women to apply healthy lifestylesin order to reduce the occurrence of dysmenorrhea and learning activities willnot be disturbed.